Quercetin ameliorates chicken quality by activating the PI3K/PKB/AMPK signaling pathway in broilers - Wang, Mi; Wang, Bo; Zhou, Shuaishuai; Liu, Jiayan; Lu, Han; Wu, Hao; Ding, Manyi; Li, Yao (Frontiers in Veterinary Science, 2022)
The present study was conducted to investigate effects and mechanism of quercetin on chicken quality in broilers. 480 AA broilers were randomly allotted to four treatments (0, 0.2, 0.4, and 0.6 g /kg) for 42 days. Compared with the control, 0.4 g/kg quercetin supplementation significantly increased pH45min and L* value of thigh muscle, and decreased shearing force of thigh muscle and breast muscle, and drip loss of thigh muscle (P<0.05). The 0.6 g/kg quercetin supplementation significantly increased pH45min and L* value of thigh muscle, pH45min of breast muscle and decreased drip loss of thigh muscle (P<0.05). Sensory score of meat color, tenderness and juiciness also were improved with increasing quercetin supplementation (P<0.05). Inosinic acid (IMP) content of breast and thigh muscle was significantly increased by 0.6 g/kg quercetin in broilers (P<0.05). 0.2, 0.4 and 0.6 g/kg quercetin supplementation significantly reduced L-FABP mRNA expression (P<0.05, P<0.05, P<0.05); 0.4 and 0.6 g/kg quercetin supplementation significantly increased mRNA expression of PKB and AMPKα1 (P<0.05, P<0.05); 0.6 g/kg quercetin supplementation significantly reduced SREBP1 and HMGR mRNA expression (P<0.05, P<0.05), significantly increased mRNA expression of CPT1 and PPARγ (P<0.05, P<0.05); 0.2, 0.4 and 0.6 g/kg quercetin supplementation significantly increased mRNA expression of PI3K, LPL and Apo A1, significantly reduced mRNA expression of ACC and FATP1 in breast muscle of broilers (P>0.05). PI3k, PKB, AMPK, SREBP1, L-FABP were significantly and positively correlated with pH45min (P<0.05); PPARγ was significantly and positively correlated with shear force (P<0.05); CPT1 was significantly and positively correlated with value of L* (P<0.05); HMGR was significantly and positively correlated with drip loss (P<0.05). In conclusion, quercetin improved the meat quality, which protected against lipid oxidation and deposition by regulating PI3K/PKB/AMPKα1 signaling pathway in breast muscle of broilers.